2009
DOI: 10.1007/s12088-009-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of Frankia from root nodules of Hippophae salicifolia D.Don found in Sikkim

Abstract: Molecular diversity of Frankia was assessed directly from the root nodules of Hippophae salicifolia naturally occurring in North Sikkim. Amplicon restriction patterns (ARPs) were developed by digesting 16S-ITS-23S amplicons with RsaI. Three ARPs were detected, showing diversity among strains of Frankia that nodulate Hippophae. This was confi rmed by sequencing one amplicon each for the three ARPs. Therefore, ARP can be used as a tool for screening amplicons for nucleotide sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The strains HsIi10 and HsIi9 of cluster I were closely related to each other while both were distantly related to the other frankial strains of cluster II i.e., HsIi8, HsIi5, HsIi11, HsIi13, HsIi12, HsIi4, HsIi14, and HsIi2. Similarly, an existence of high degree of genetic variation has been recently reported by Khan et al (2009) among the Frankia strains isolated from Hippophae salicifolia found in Sikkim which was based on RFLP analysis of 16S-ITS-23S amplicons.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The strains HsIi10 and HsIi9 of cluster I were closely related to each other while both were distantly related to the other frankial strains of cluster II i.e., HsIi8, HsIi5, HsIi11, HsIi13, HsIi12, HsIi4, HsIi14, and HsIi2. Similarly, an existence of high degree of genetic variation has been recently reported by Khan et al (2009) among the Frankia strains isolated from Hippophae salicifolia found in Sikkim which was based on RFLP analysis of 16S-ITS-23S amplicons.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, Frankia strains isolated from the root nodules of Hippophae salicifolia D. Don found in North Sikkim has been studied but only on the basis of restriction pattern analyses of 16S-ITS-23S amplicon (Khan et al 2009). However, no reports are available that deal with the detailed physiological, biochemical and molecular characterization of Frankia strains isolated from root nodules of Hippophae salicifolia D. Don.…”
Section: Introductionmentioning
confidence: 99%
“…The selected study area ranged in elevation from 2127 to 3150 m above sea level, a difference of 1023 m characterized by craggy configurations of monolithic cliffs, high slopes, with change in the temperature ranging from +25 °C (during summers) to −30 °C (during winters). The collection was done in the month of October as it has been previously mentioned by Varghese and Khan et al that the best growth of Frankia nodules was observable after the monsoon season. Five plants on the hillside and five plants on the riverside were selected on a random basis with care being taken that the underground lateral roots of the plant were at least one meter away from each other.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, 16S rRNA gene sequences have also been used to discriminate between closely related frankiae . The ITS region between 16S and 23S rRNA has also been used to discriminate between Frankia strains at molecular level . Further, genetic relatedness among the Frankia strains has also been evaluated using nif gene sequences .…”
Section: Introductionmentioning
confidence: 99%
“…Frankia sp. have also been characterized using physiological, biochemical, molecular approaches (Normand et al 1996 ; Singh et al 2010 ) and RFLP-based analyses of 16S-ITS of Frankia (Khan et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%